2006
DOI: 10.2353/ajpath.2006.050001
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Hedgehog Signaling in Chondrosarcoma Up-Regulates Tumor Cell Proliferation

Abstract: Chondrosarcoma is a malignant cartilage tumor that may arise from benign precursor lesions, such as enchondromas. Some cases of multiple enchondromas are caused by a mutation that results in constitutive activation of Hedgehog-mediated signaling. We found that chondrosarcomas expressed high levels of the Hedgehog target genes PTCH1 and GLI1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
122
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(123 citation statements)
references
References 45 publications
1
122
0
Order By: Relevance
“…To circumvent this issue, mice with the same tamoxifen-induced expression of crerecombinase in chondrocytes were crossed with conditional beta-catenin floxed mice, resulting in stabilization of beta-catenin 91 107 . Similar to the dose and efficacy of cyclopamine, the small molecule N-…”
Section: Developmental Signaling Pathways In Post Natal Chondrocytesmentioning
confidence: 99%
“…To circumvent this issue, mice with the same tamoxifen-induced expression of crerecombinase in chondrocytes were crossed with conditional beta-catenin floxed mice, resulting in stabilization of beta-catenin 91 107 . Similar to the dose and efficacy of cyclopamine, the small molecule N-…”
Section: Developmental Signaling Pathways In Post Natal Chondrocytesmentioning
confidence: 99%
“…Previous studies have shown that the hedgehog signaling pathway, a major regulator of the cell cycle and differentiation in chondrocytes (29), was constitutively active in primary chondrosarcomas (30). Since MATN3 is believed to intervene in hedgehog regulation of chondrogenesis (10,31), overexpression of hedgehog signaling and overexpression of MATN3 might be functionally linked.…”
Section: Discussionmentioning
confidence: 99%
“…The hedgehog (Hh) signaling pathway is constitutively active in enchondromas and chondrosarcomas (8,9). Hh is important in growth-plate chondrocyte differentiation, where it cooperates with parathyroid hormone-like hormone in a negative feedback loop to inhibit the differentiation of proliferative growth-plate chondrocytes (6,(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%